Reliable Software Technologies – Ada-Europe 2014 19th Ada-Europe International Conference on Reliable Software Technologies, Paris, France, June 23-27, 2014. Proceedings - George, Laurent; Vardanega, Tullio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 19th Ada-Europe International Conference on Reliable Software Technologies, Ada-Europe 2014, held in Paris, France, in June 2014. The revised 12 full papers presented together with two keynotes were carefully reviewed and selected from 68 submissions. They are organized in topical sections on formal methods; uses of ada; real-time scheduling; applications.
Formal methods -- Uses of ada -- Real-time scheduling -- Applications.
Keywords: Programming languages (Electronic computers).; Software engineering; Special purpose computers; Computer logic; Mathematical logic; Programming Languages, Compilers, Interpreters; Software Engineering; Special Purpose and Application-Based Systems; Logics and Meanings of Programs; Mathematical Logic and Formal Languages